A comparative study on regional cerebral oxygen saturation and central venous oxygen saturation as predictors of outcome in patients on off-pump coronary artery bypass graft surgery - Kundu, Shruti; Roy, Sankar; Sur, Debajyoti; Biswas, Arunava (Asian Journal of Medical Sciences, 2022)
Background: Off-pump coronary artery bypass grafting (OPCABG) is a common and acceptable surgery. Aims and Objectives: The study was conducted to compare central venous oxygen saturation (ScvO2) and regional cerebral oxygen saturation (rSO2) to see which of the two is better predictor for the prognosis of patients undergoing OPCABG. Heart rate (HR), invasive blood pressures, and partial pressure of oxygen (pO2) have also been recorded to see if they are independent predictors of prognosis in OPCABG patients. Materials and Methods: A total of 56 patients undergoing OPCABG were included in the study. Baseline values and intraoperative values of ScvO2, rSO2, HR, systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), pO2 at different time periods were recorded. Post-operatively the patient was shifted to intensive care unit (ICU) in intubated condition, and time to extubation since shifting to ICU was noted. Results: The ScvO2 values after sternal closure (correlation coefficient r=−0.4821, P=0.0002), and on shifting to ICU (correlation coefficient r=−0.4575, P=0.0004) showed good correlation with time to extubation. Similarly, the rSO2 values after sternal closure (correlation coefficient r=−0.5198, P<0.0001) and on shifting to ICU (correlation coefficient r=−0.5498, P<0.0001) showed good correlation with time to extubation. HR SBP, DBP, MAP, pO2 individually did not show any correlation with time to extubation (P>0.05). Conclusion: ScvO2 and rSO2 both have strong correlation with time to extubation and are capable of predicting prognosis in OPCABG patients.